Phytochemical Test and Antioxidant Activity of Methanol Extract in Arabica Coffee Leaves by Using DPPH Method (1,1-Diphenyl-2-Picrylhydrazyl) - Rosalina Yuliana Kurang; Rinda Yunita Kamengon (Walisongo Journal of Chemistry, 2021)
The use of coffee plants is more focused on the coffee beans as a brewing drink or as a food additive. Parts of the coffee plant, such as leaves, are considered waste and have not been properly utilized. This study aimed to determine the phytochemical content and antioxidant activity of the methanol extract in Arabica coffee (Coffea arabica) leaves. The method used in this study was the extraction and DPPH method (1,1-diphenyl-2-picrylhydrazyl). The results showed that the Arabica coffee leaves contained flavonoids, alkaloids, terpenoids, and phenolic compounds. The antioxidant activity test showed an IC50 value of 57.699 ppm with the strong antioxidant category.